Discursive analysis of the song “Bandera Blanca” by Camila (Orkopata. Revista de Lingüística, Literatura y Arte, 2023)
This article examines the song "Bandera Blanca" by the group "Camila" from a hermeneutic and discursive perspective. The importance of music in various fields is highlighted, such as recreational, creative, emotional, cultural and psychological, since over the years it has been used and interpreted in multiple ways. The combination of rhythms and lyrics is used to convey messages and emotions. Therefore, considering this relevance, the symbolism of the song and the relationship it establishes between a courtship and a chaotic situation that leads to surrender are analyzed from a perspective generated by discursive analysis through hermeneutics, where each away from the song, interpreting and analyzing from its literal, symbolic and emotional phases, as well as the enunciative, locutive, perlocutive and hyperlocutive phases. The analysis concludes that the letter shows the narrator's struggle to find stability and love in the midst of adversity, but finally reaches a point of surrender and acceptance of personal limitations; while at a theoretical level the importance of music is identified personally, in development, economics and different dimensions.
Keywords: analysis; song; discourse; hermeneutics; interpretation